The characteristics of geriatric patients managed within the resuscitation unit of a district-level emergency centre in Cape Town - Simakoloyi, Natalie (Stellenbosch : Stellenbosch University, 2020)
Thesis (MFamMed)--Stellenbosch University, 2020.